Odpowiedź :
Odpowiedź:
[tex]a) \: 4 \frac{3}{7} + 1 \frac{1}{5} = 4 \frac{15}{35} + 1 \frac{7}{35} = 5 \frac{22}{35} [/tex]
[tex]b) \: 5 \frac{2}{3} - 2 \frac{1}{4} = 5\frac{8}{12} - 2 \frac{3}{12} = 3 \frac{5}{12} [/tex]
[tex]c) \: 4\frac{3}{10} - 2 \frac{1}{5} = 4 \frac{6}{20} - 2 \frac{4}{20} = 2 \frac{2}{20} = 2 \frac{1}{10} [/tex]
[tex]d) \: 3 \frac{2}{9} + 1 \frac{5}{6} = 3 \frac{4}{18} + 1 \frac{15}{18} = 4 \frac{19}{18} = 5 \frac{1}{18} [/tex]
[tex]e) \: 7 \frac{3}{4} - 5 \frac{1}{3} = 7 \frac{9}{12} - 5 \frac{4}{12} = 2 \frac{5}{12} [/tex]
[tex]f) \: 4\frac{2}{15} + 2 \frac{7}{10} = 4 \frac{4}{30} + 2 \frac{21}{30} = 6 \frac{25}{30} = 6 \frac{5}{6} [/tex]
[tex]g) \: 11 \frac{1}{11} + 3 \frac{2}{33} = 11 \frac{3}{33} + 3 \frac{2}{33} =14 \frac{5}{33} [/tex]
[tex]h) \: 4 \frac{5}{7} - 1 \frac{1}{2} = 4\frac{10}{14} - 1 \frac{7}{14} = 3 \frac{3}{14} [/tex]
[tex]i) \: 2 \frac{3}{7} - \frac{2}{5} = 2 \frac{15}{35} - \frac{15}{35} = 2 \frac{1}{35} [/tex]
Pozdrawiam.